2013
DOI: 10.3945/ajcn.112.038737
|View full text |Cite
|
Sign up to set email alerts
|

Dietary amino acids and the risk of hypertension in a Dutch older population: the Rotterdam Study

Abstract: Our data do not suggest a major role for glutamic acid, arginine, lysine, tyrosine, or cysteine intake (as % of protein intake) in determining population BP or risk of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 25 publications
5
40
2
3
Order By: Relevance
“…In accordance with the present results, the Rotterdam study also showed no association between incident hypertension and several amino acids, such as arginine, lysine, glutamic acid, cysteine, and tyrosine. 34 In addition, serine and glycine were not considered by the Rotterdam study. 34 Although a large number of lipids of different classes were measured in this study, only 4 phosphatidylcholines metabolites (acyl-alkyl-phosphatidylcholines C42:4, C44:3, diacylphosphatidylcholines C38:3, and diacyl-phosphatidylcholines C38:4) were identified to be predictive to a certain extend for incident hypertension during the 10 years of follow-up time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the present results, the Rotterdam study also showed no association between incident hypertension and several amino acids, such as arginine, lysine, glutamic acid, cysteine, and tyrosine. 34 In addition, serine and glycine were not considered by the Rotterdam study. 34 Although a large number of lipids of different classes were measured in this study, only 4 phosphatidylcholines metabolites (acyl-alkyl-phosphatidylcholines C42:4, C44:3, diacylphosphatidylcholines C38:3, and diacyl-phosphatidylcholines C38:4) were identified to be predictive to a certain extend for incident hypertension during the 10 years of follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, serine and glycine were not considered by the Rotterdam study. 34 Although a large number of lipids of different classes were measured in this study, only 4 phosphatidylcholines metabolites (acyl-alkyl-phosphatidylcholines C42:4, C44:3, diacylphosphatidylcholines C38:3, and diacyl-phosphatidylcholines C38:4) were identified to be predictive to a certain extend for incident hypertension during the 10 years of follow-up time. The partial plots suggest a protective role of the 2 acyl-alkylphosphatidylcholines C42:4 and C44:3 with increasing concentrations while only a certain concentration range of the diacyl-phosphatidylcholines C38:4 was protective regarding incident hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rotterdam Study suggested no major role for cysteine, glutamic acid, arginine, lysine or tyrosine intake in determining blood pressure in a cross-sectional analysis. 20 There was also no association between intake of the 5 amino acids and risk of developing hypertension during 6 years of follow-up. 20 Mean cysteine intake was much higher in the Rotterdam Study (≈600 mg cysteine per 1000 kcal) than in our study (≈360 mg cysteine per 1000 kcal).…”
Section: Discussionmentioning
confidence: 94%
“…The intake of glutamic acid, arginine, lysine, tyrosine and cysteine from food plays an important role in hypertension [17]. Among dietary factors, carbohydrates, sodium are risk factors for hypertension, and animal protein, riboflavin, niacin, calcium, phosphorus, zinc, magnesium, potassium, animal iron [18], potassium [19] are protective factors for hypertension.…”
Section: Discussionmentioning
confidence: 99%